2018
DOI: 10.18865/ed.28.s2.475
|View full text |Cite
|
Sign up to set email alerts
|

Engaging African American Veterans with Health Care Access Challenges in a Community Partnered Care Coordination Initiative: A Qualitative Needs Assessment

Abstract: Veterans living in underserved areas who have had difficulty accessing VA care have unique perspectives on VA services. Partnering with trusted local community organizations to engage Veterans in their home communities is a promising strategy to inform efforts to improve care access and coordination for vulnerable Veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…65 This, in turn, makes African American communities wary of engaging in research, 15,21,[69][70][71] as well as taking vaccines, [60][61][62] receiving antiretroviral therapy, 72 or considering kidney transplants. 73,74 To make matters worse, broader systemic issues are cast in the background, including limited access to health care 75 and timely dementia diagnoses 3 for African Americans, high costs, 76 and bias on behalf of medical providers (specifically in the area of who is eligible for transplantation), 77 which creates and sustains health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…65 This, in turn, makes African American communities wary of engaging in research, 15,21,[69][70][71] as well as taking vaccines, [60][61][62] receiving antiretroviral therapy, 72 or considering kidney transplants. 73,74 To make matters worse, broader systemic issues are cast in the background, including limited access to health care 75 and timely dementia diagnoses 3 for African Americans, high costs, 76 and bias on behalf of medical providers (specifically in the area of who is eligible for transplantation), 77 which creates and sustains health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in Health Care Providers Among Veterans and Active Duty Military the past several decades, medical mistrust has emerged as an important and prevalent public health problem (e.g., Izquierdo et al, 2018). According to one survey, only 23% of Americans express a great deal or quite a lot of confidence in the health care system (Richmond, 2021).…”
Section: Listen To Your Commandermentioning
confidence: 99%
“…In a systematic review of studies examining the effect of race on patient-provider communication, the majority of studies measuring the quality of patient-physician communication found lower quality communication for Black patients (32). Other studies have found that, compared to White patients, Black patients are less satisfied with their communication with physicians, reported receiving less information (33)(34)(35)(36)(37) from their physician (38,39), experiencing less partnership building (40), and were less likely to be asked to participate in treatment decision-making (40)(41)(42)(43). They also reported experiencing more negative affect from physicians (44,45) and are given less time to talk and have shorter visit times (38,46).…”
Section: Introductionmentioning
confidence: 99%